The psychology of conviction;: a study of beliefs and attitudes - Jastrow, Joseph (H. Mifflin, 1918)
The psychology of conviction.--Belief and credulity.--The will to believe in the supernatural.--The case of Paladino.--The antecedents of the study of character and temperament.--Fact and fable in animal psychology.--"Malicious animal magnetism."--The democratic suspicion of education.--The psychology of indulgence: alcohol and tobacco.--The feminine mind.--Militarism and pacifism.